Optimal design of agro-residue filled poly(lactic acid) biocomposites using an integrated CRITIC-CoCoSo multi-criteria decision-making approach - László Lendvai; Sándor Kálmán Jakab; Tej Singh (Scientific Reports)
Abstract In recent years, there has been a rise in environmental awareness, leading to increased efforts to develop eco-friendly materials as alternatives to petroleum-based polymers. This study examined the performance optimization of poly(lactic acid) (PLA) biocomposites filled with agricultural byproducts at concentrations ranging from 0 to 20% by weight, highlighting their potential as substitutes for commodity plastics. The agro-residues used as fillers were flax seed meal and rapeseed straw. A hybrid decision-making algorithm was proposed, utilizing the “criteria importance through inter-criteria correlation” (CRITIC) alongside the “combined compromise solution” (CoCoSo), aimed at identifying the optimal alternative among the evaluated samples. The algorithm considered several attributes, including mechanical traits evaluated via tensile, flexural, and impact tests, hardness, water absorption, biodegradation, and production cost. The findings revealed that the strength properties, including tensile, flexural, impact, and water absorption, were most advantageous for neat PLA. In contrast, the highest modulus values were recorded for the biocomposite filled with 20 wt% rapeseed straw. The biocomposites exhibit increased hardness as agro-waste content rose, with the highest hardness observed in the biocomposite filled with 20 wt% flax seed meal. The study on biodegradation indicates that a higher content of agro-waste promotes disintegration, with flax seed meal emerging as the most effective additive in this context. The findings show that adding various agricultural byproducts in varying amounts affects the evaluated properties differently. Hence, the hybrid CRITIC-CoCoSo optimization approach is utilized to choose the optimal biocomposite. The findings show that the biocomposite with 20 wt% rapeseed straw demonstrated optimal physico-mechanical and biodegradation properties, making it a promising eco-friendly alternative for future applications.